An Analysis of India's Need of Capacity Building for e-Governance - Jindal, Neena; Sehrawat, Anil; Medury, Y. (Prabandhan: Indian Journal of Management, 2016)
Capacity building of municipal functionaries is recognized as an approach to make strong municipal work practices and to improve the achievements of municipalities in India. The main purpose of this paper was to describe the social, economic, and educational status of the people and evaluate their readiness for the e-governance practices and capacity building requirements for the community. The paper attempted to throw light on the need and approaches of the community development by building their capacity. The findings of this research are based on the perceptions of personal observation of the ground realities. The study is an attempt to point that the capacity building initiative is a must for the people in almost all the states local municipalities. People in India need to be empowered by adequate training and education. This paper is based on a randomly selected population scattered geographically in six Northern Indian states. In every state, 150 questioners were distributed; there were a total of 900 questioners distributed among the population, out of which only 710 questioners with a 78.9% response rate were received back. The analysis presents the picture of the demographic status of the citizens. So, at the end, it is concluded that the Central and State government should put extra efforts to find out and tackle the growing needs of municipalities in order to have a greater impact of e-governance.